Angiographic Severity of Coronary Artery Disease in Diabetic and Non-diabetic Acute STEMI Patients in a Tertiary Care Centre of Nepal - Pathak, S. R.; Gajurel, R. M.; Poudel, C. M.; Shrestha, H.; Thapa, S.; Thapa, S.; Koirala, P. (Kathmandu University Medical Journal, 2021)
Background Patients with diabetes mellitus have a higher prevalence of atherosclerotic heart disease and a higher incidence of myocardial infarction than the general population. Definitive diagnosis and precise assessment of anatomic severity of Coronary Artery Disease requires invasive diagnostic modality like coronary angiography. Objective To study angiographic characteristics and severity involving coronary arteries in patients with acute ST segment elevation Myocardial infarction and to compare the same in diabetics and non-diabetics. Method Among 150 patients with acute coronary syndrome, 75 diabetics and 75 nondiabetics admitted in Manmohan Cardiothoracic vascular and transplant Centre were selected randomly during a period of one year formed the study group. Random Blood Sugar, Fasting Blood Sugar was done in all 150 patients, HbA1c in all diabetics. All subjects with acute ST Elevation Myocardial Infarction were taken up for coronary angiography intended for primary PCI. Result In our study, 35 (46.7%) out of 75 diabetic patients had triple or multi-vessel disease compared to 10 (13.4%) out of 75 non diabetics. Non-diabetic patients had significantly higher single vessel disease (65.3%). There was a statistically significant association of duration of DM with vessels involved. The occurrence of Triple Vessel Disease/Multivessel Disease was significantly higher in the patients with DM duration > 10 years compared to patients with DM duration < 10 years (64.7% vs. 35.3%, P < 0.001), however there was no significant difference in type of vessel involved. Similarly, a significantly higher proportion of Triple vessel disease was observed in patients with poor glycemic control (HbA1c > 8.5%). 72.2% of the patients with HbA1c > 8.5% had Triple vessel disease/Multi vessel disease, whereas patients with good glycemic control (HbA1c < 7.0%) had predominantly Single vessel disease (90.0%), with no occurrence of Triple vessel disease/Multi vessel disease Conclusion Diabetic patients presenting with ST Elevation Myocardial Infarction are likely to have triple/multiple vessel disease compared to non-diabetic patients. The occurrence of Triple Vessel Disease/Multivessel Disease was significantly higher in the patients with DM duration > 10 years compared to patients with DM duration <10 years.